MAPPING RESEARCH DEVELOPMENTS AND TRENDS: SUSTAINABLE ECONOMIC LITERACY IN ISLAMIC CONTEXT - Mukti, Titania (Universitas Islam Indonesia, 2025)
This study presents a bibliometric analysis of islamic sustainable economic research from scopus indexed scientific publications. Data sources were obtained from searches using the publish or perish application with the keywords “islamic AND sustainable AND economy” total of 205 articles from 2007-2024. Statistical analysis of metadata using the VOS Viewer application. This study analyzes the trend of research development based on the year of publication, journal contribution, journal citation, country, co-authorship, authors, keywords used, and visualization analysis of the research landscape cluster. The results show that the keywords